Psychological perspectives in HIV care : an inter-professional approach - Croston, Michelle; Rutter, Sarah (Clinical psychologist) (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book provides an accessible introduction for healthcare professionals who work with people living with HIV"--
Chapter 1: The good, the bad and the ugly: How do people living with HIV experience care in the health system? Author: Dr India Amos, Clinical psychologist and Lecturer in counselling and psychology at Salford University, Roland Chesters, Campaigner for Disability and author of Ripples from the edge of life. Chapter contributors: Angelina Namiba and Merial Rattue -- Chapter 2: Self -Awareness in HIV care. Author: Caroline Ridley, Senior Lecturer in adult nursing, Manchester Metropolitan University -- Chapter 3: Seeing the whole person : A biopsychosocial perspective in HIV care. Author: Dr Gemma Paszek, Clinical Psychologist, HIV Service, Central Manchester University Hospital NHS Foundation Trust, Dr Kathryn Bourne, Clinical Psychologist, HIV Service, NMGH -- Chapter 4: HIV Diagnosis: The impact on mental health and wellbeing. Author: James Meeks, Senior Lecturer, Sexual Health, School of Community Health and Midwifery, University of Central Lancashire , Emma Jones ,Senior Lecturer, Mental Health, School of Nursing, University of Central Lancashire -- Chapter 5: Stormy waters: difficult conversations in HIV care. Author: Dr Michelle Croston, Senior lecturer/HIV specialist nurse, Manchester Metropolitan University / North Manchester General Hospital and Dr Stuart Gibson Clinical Psychologist, Barts Hospital, London -- Chapter 6: Traumatic beginnings, complicated lives: Attachment styles, relationships and HIV care. Author: Dr Sam Warner, Consultant Clinical Psychologist/Honorary Lecturer, School of Social Science, Salford University and Dr Sarah Rutter, Clinical Psychologist, HIV Service, North Manchester General Hospital -- Chapter 7: Chemsex among men who have sex with men: a social psychological approach. Author Dr Rusi Jaspal, De Montfort University, Leicester, UK,Abo Akademi University, Turku, Finland -- Chapter 8: The seemingly intractable problem of HIV-related stigma: developing a framework to guide stigma interventions with young people living with HIV. Author: Dr Tomas Campbell, Clinical psychologist -- Chapter 9: Multidisciplinary management of neuropathic pain in HIV care. General Authors: Dr Sarah Blackshaw, Highly Specialist Clinical Psychologist Manchester and Salford Pain Centre, Salford Royal Hospital, Manchester, Dr HooKee Tsang, Consultant Anaesthetist Pain Clinic, Broadgreen Hospital, Liverpool, Mrs Catherine Heaton, Senior Physiotherapist, The Walton Centre Liverpool -- Chapter 10: The psychological impact of ageing with HIV. Author: Shaun Watson, HIV community specialist nurse, Chelsea and Westminster hospital and Dr Alexander Margetts, Clinical Psychologist, CNWL NHS Foundation Trust -- Chapter 11: Neurocognitive issues for adults in HIV care. Author: Dr Alexander Margetts, Clinical Psychologist, CNWL NHS Foundation Trust and Dr Tomas Campbell, Clinical psychologist.
OCLC-licensed vendor bibliographic record.
Keywords: HIV-positive persons -- Care; HIV-positive persons -- Psychology; HIV-positive persons -- Medical care; HIV infections -- Psychological aspects; AIDS (Disease) -- Psychological aspects; Medical personnel and patient; MEDICAL / AIDS & HIV; MEDICAL / Nursing / Nurse & Patient